أثر قطاع التأمين على النمو الإقتصادي دراسة حالة (الجزائر والمغرب ومصر) - بلعباس وئام; مشراوي فاطمة الزهراء; عامر إبراهيم (جامعة عمار ثليجي الاغواط, 2022)
This study aims to test the impact of the insurance sector on economic growth in three countries: Algeria, Egypt, and Morocco, during the time period (2000-2018), using annual data for two independent variables (penetration rate, loans granted to the private sector), and the growth rate as a dependent variable, the Panel ARDL model was employed to verify the existence of a long- and short-run equilibrium relationship between the variables. The results of the long-term estimation showed that the independent variables, the percentage of loans granted to the private sector (CR), and the penetration rate (Pin) are not significant at 0.05, but the variable CR is statistically significant at 0.1, where there is an inverse relationship with economic growth. As for the relationship in the short term, it is noted from the outputs of the error correction model estimation that correcting the imbalances between the short and long term takes place approximately in the same year. The existence of an inverse relationship between the loans granted and economic growth, which can be explained by the weakness and inefficiency of the banking sector and the presence of structural defects in the economies of these countries in general When the error correction model was estimated using only two variables, the penetration rate and the economic growth rate, the results showed that Morocco is relatively superior to Algeria and Egypt in terms of the impact of the insurance sector on economic growth.